Valoração econômica dos danos ao patrimônio cultural: o caso da demolição da Chácara Flora - Sá, Marcos Paulo de Oliveira (2022)
Despite its constitutional protection and its diverse values for society, cultural goods are increasingly threatened by degradation, mainly by human activities. As they are not traded on the market and do not have a price or value that we can directly observe, it is necessary to apply economic valuation methods as a way to obtain a scientifically based indemnity value to subsidize remedial lawsuits. Based on the methodology of economic valuation created by the Council for the Defense of the Historical, Archaeological, Artistic and Touristic Heritage of the State of São Paulo (CONDEPHAAT), the present work has as a general objective to analyze it and propose adaptations that allow it to add requirements of speed, legal certainty and reliability of the economic valuation process of material cultural assets (buildable) for use in civil liability lawsuits. Specifically, this study intends to analyze the advantages and disadvantages of the main methods of economic valuation of material cultural heritage damages, in particular those of CONDEPHAAT and Professor Georges Kaskantzis, to later propose the inclusion of the Replacement Cost methodology as the basis of calculation for the CONDEPHAAT methodology and apply it to a case study, namely the demolition of Chácara Flora, located in the municipality of Fortaleza, Ceará.